Longitudinal Immunological Analysis of Portuguese Healthcare Workers Across the COVID-19 Pandemic Reveals Differences in the Humoral Immune Response to Vaccines - Luísa Vilela; Anabela Silva; Alberta Cruz; Madalena Sousa; Margarida Costa; Fernando Fonseca; Susana Campino; Taane G. Clark; Anabela Miranda (Vaccines)
Background: A vaccination programme against severe acute respiratory syndrome coronavirus 2 was initiated in Portugal in December 2020. In this study, we report the findings of a prospective cohort study implemented with the objective of monitoring antibody production in response to COVID-19 vaccination. Methods: The humoral immune response to vaccination was followed up using blood samples collected from 191 healthcare workers. Participants were split into three groups: the Oxford-AstraZeneca (Vaxzevria) vaccine group (n = 68), the Pfizer-BioNTech COVID-19 (Comirnaty) vaccine group (n = 51), and the Post-COVID group (n = 72). The kinetics of anti-spike antibody production were evaluated until 56 days on average after the third dose (booster). Results: We observed that antibody titres peaked approximately one month after full vaccination and declined steadily thereafter. We also found that mRNA vaccination induces higher titres of antibodies than viral vector vaccination, and both generate greater antibody responses than mild or moderate COVID-19. Additionally, whilst the booster for the Oxford-AstraZeneca and Pfizer-BioNTech groups led to antibody levels higher than those at any previous sample collection point, the booster for the Post-COVID group (persons with a history of COVID-19 prior to vaccination) led to antibody levels lower than those attained one month after the second dose. Interpretation: Our results indicate that there are different kinetics of antibody production between individuals who received the Pfizer-BioNtech mRNA vaccine and those who received the Oxford-AstraZeneca vector vaccine, or individuals who had COVID-19 before being vaccinated. Additionally, we observed that exposure to either natural infection or vaccination modulates the response to subsequent vaccination. This is particularly evident after administration of the third dose to the Post-COVID group, where our findings point to a hindrance in vaccine boosting, probably due to unwanted feedback by high titres of pre-existing antibodies.